Identifikasi Loyalitas Pelanggan dengan Kepuasan Sebagai Variabel Intervening Pada Toko Grosir HR Losari Kecamatan Cilongok Kabupaten Banyumas - Sulasih, Sulasih; Parno, Parno; Trianingsih, Ade; Intansari, Anggita Isty (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to determine whether product diversity, perceived value, and location have an effect on customer loyalty with customer satisfaction as a mediating variable at the HR Losari Wholesale Store, Cilongok District, Banyumas Regency. The quantitative research method and analysis tool used in this study are Smart-PLS 4. The sample collection method uses non-probability sampling with a purposive sampling technique so that 385 respondents are produced. The results of this study indicate that perceived value and location have a significant effect on customer loyalty with strong validity and reliability tests. However, product diversity does not have a significant effect on customer loyalty. Product diversity, perceived value, and location have a significant effect on customer satisfaction. The intervening variable of customer satisfaction can also mediate the relationship between Product diversity, perceived value, and location on customer loyalty